2001
DOI: 10.1034/j.1600-0609.2001.5790508.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased plasma activity of antithrombin or protein C is not due to consumption coagulopathy in septic patients with disseminated intravascular coagulation

Abstract: We investigated whether depressed plasma antithrombin and protein C activity, considered as a specific finding of disseminated intravascular coagulation (DIC), is due to consumption coagulopathy in septic patients with DIC. An analysis of hemostatic parameters was performed in 139 septic patients (68 with DIC and 71 without DIC). Plasma activity of antithrombin and protein C tended to be significantly decreased in septic patients with DIC but not in those without DIC (p < 0.001). However, when the septic patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 25 publications
(36 reference statements)
7
32
1
2
Order By: Relevance
“…However, in this study, we found no correlations between TAT and AT activity in the pre-administration phase in critical patients with DIC. Furthermore, TAT is believed to be uncorrelated with AT activity because the total amount of AT in the body is so enormous that AT levels would not decrease even after remarkable TAT production [35]. Therefore, the present results confirm the data of the previous paper [35].…”
Section: Relations Of At Activity and Tat Or Albumin Levelssupporting
confidence: 83%
See 1 more Smart Citation
“…However, in this study, we found no correlations between TAT and AT activity in the pre-administration phase in critical patients with DIC. Furthermore, TAT is believed to be uncorrelated with AT activity because the total amount of AT in the body is so enormous that AT levels would not decrease even after remarkable TAT production [35]. Therefore, the present results confirm the data of the previous paper [35].…”
Section: Relations Of At Activity and Tat Or Albumin Levelssupporting
confidence: 83%
“…Therefore, it is possible that the serum albumin level could be a reliable index for estimating changes in the post-administration AT levels in critical patients with DIC. Furthermore, this study supports a previous paper [35] that in septic patients with DIC, AT could be decreased by enhanced vascular permeability rather than its consumption. …”
Section: Relations Of At Activity and Tat Or Albumin Levelssupporting
confidence: 80%
“…PT, fibrinogen, platelet count, and fibrin and FDP were measured in each institutes based on numerous previous reports [16][17][18]. An FDP assay in each institute correlated well with LPIA FDP (Mitsubishi Chemical Medience Corporation, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The inflammation mediators induced by thrombotization lead to further coagulation activation by suppressing natural coagulation inhibitors -antithrombin, activated protein C and TFPI (ref. 28,29 ). Products of activation of TF -F IIa, F VIIa, Xa -cause further overexpression of tissue factor, which closes the vicious circle: thrombosis-inflammationthrombosis, linked by tissue factor 30,31 .…”
Section: Tissue Factor -Regulation Of Its Expressionmentioning
confidence: 99%